Genome sequencing and multi-stage, blood-feeding, and tissue-specific transcriptome atlas of the Rocky Mountain wood tick provide a critical resource for this vector - Joshua E. Tompkin; Perot Saelao; Justyna Kruczalak; Huiqing Yeo; Pia U. Olafson; Sheina B. Sim; Kennan Oyen; Melissa Kelley; Renee L. Corpuz; Brian Scheffler; Scott M. Geib; Anna K. Childers; et al. (Insect Biochemistry and Molecular Biology, 2026)

Demography and Localized Reservoirs of Diversity Underlie Global Divergence in the Giant Kelp Macrocystis pyrifera - E. C. Giles; A. Zaiko; H. G. Hampton; P. Saenz‐Agudelo; M. Scriver; D. Crossett; A. Sim; X. B. Zhang; T. Jedrecka; C. O. Blain; L. Rauhina‐August; C. E. Cornwall; et al. (Molecular Ecology, 2026)
Accurate assessments of genetic diversity are crucial for effective management of natural resources. Numerous evolutionary mechanisms and genetic constraints can shape lineage divergence, challenging our quantification of biodiversity. Here, using whole genome resequencing of globally distributed giant kelp, Macrocystis pyrifera (Order: Laminariales), we show clear separation of genetic groups across the Pacific based on 99 genotyped individuals and 799,160 SNPs. Additionally, divergence across 88 genotyped individuals (53 derived in silico and 35 newly sequenced) considering 5,466,408 SNPs is attributed to both historical demographic processes and differential selection. Between Central California and the South Pacific (Chile, Tasmania, New Zealand), high divergence has occurred with very weak levels of gene flow, with concurrent timing of divergence. In parts of the South Pacific, kelp exhibited nucleotide diversity comparable to Central Californian populations but showed stronger signals of directional selection and excesses of rare alleles, with fewer genes showing signs of negative selection and some carbon‐related genes under positive selection. In contrast, Central Californian kelp had an excess of genes with synonymous mutations and showed evidence of a recent population contraction, as indicated by linkage disequilibrium and Tajima's D . In all populations, genome‐wide background divergence was paired with narrow genomic intervals of high nucleotide diversity and high linkage disequilibrium, which predominantly contained pervasive repetitive sequences. These repetitive regions were larger and more often shared among genetic groups in the South Pacific. They also appear to harbour genes of unknown function and alleles at intermediate frequency, suggesting that giant kelp maintain reservoirs of diversity within linked repeats, and this phenomenon is more pronounced in South Pacific M. pyrifera . Overall, the discovery of differential selection and structural variation as key drivers of divergence points to underappreciated genomic mechanisms of adaptation in kelp. These results will be useful for informing efforts to enhance climate resilience by identifying the evolutionary potential underlying kelp forest adaptation in the future.

Distribution and taxonomic composition of leptocephali and hydrographic structure from New Zealand to the South Equatorial Current - Michael J. Miller; Shun Watanabe; Robert Schabetsberger; Nioka Behan-Kitto; Grace F. Cawley; Niamh Smith; Alisha M. Gill; Alexandre Che-Pelicier; Juliet E. Saul; Abigail Sim; Therese C. Miller; Sajini Dissanayake; et al. (Regional Studies in Marine Science, 2026)

Diverse prokaryotic strategies associated with soil organic matter priming - M. Waibel; E. Paterson; T.E. Freitag; F. Abram; P.E. Hedley; J. Morris; L.J. Robinson; A. Sim; B. Thornton; F.P. Brennan (Applied Soil Ecology, 2026)

Inhibition of Microcystis aeruginosa Kützing by seven submerged macrophytes and the influence of season and decomposing plant leachate - Huy A. Luong; Ann-Marie Rohlfs; Jordan A. Facey; Anne Colville; Darren Z. H. Sim; Simon M. Mitrovic (Hydrobiologia, 2026)

Exploring MAO inhibitory activity of 5-hydroxy regioisomers of hispidol’s analogs leads to identification of novel highly selective MAO-B open-conformation inhibitors - Ahmed H. E. Hassan; Rium Kim; Sung Yeun Yoo; Lamiaa O. El-Halaby; Selwan M. El-Sayed; Minji Kim; Hyeon Jeong Kim; Ki Duk Park; Jaehoon Sim; Yong Sup Lee (Molecular Diversity, 2026)

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Genomic analysis of Vanessa tameamea, the threatened Hawaiian endemic butterfly, reveals population genetic structure relevant to conservation efforts - Haley E. Arnold; Julian R. Dupuis; Daniel Rubinoff; William P. Haines; Michael San Jose; Renee L. Corpuz; Angela N. Kauwe; Tyler J. Simmonds; Scott M. Geib; Sheina B. Sim (Conservation Genetics, 2025)
Patterns of divergence and speciation on islands have long been of interest in the broader study of evolution. Hawaiʻi’s endemic Kamehameha butterfly ( Vanessa tameamea ) is experiencing population decline, but because of its high vagility and assumed genetic homogeneity as a species, its population structure has not been investigated. To evaluate V. tameamea genetic variation across the Hawaiian Islands, we assembled a reference quality genome assembly for the species using HiFi and HiC reads and performed range-wide population genetic analyses using ddRAD sequencing data. A discriminant analysis of principal components (DAPC) revealed that, contrary to prior assumptions, V. tameamea populations appear to be diverging based on geography, in a pattern similar to other native Hawaiian terrestrial arthropods. Specifically, through demographic history analyses, we find that the distinct population on Kauaʻi is likely to be ancestral, the central islands of Maui, Molokaʻi, and Oʻahu comprise another population, and Hawaiʻi Island forms a third population, with likely more gene exchange with the central islands. Finally, we investigate the SNPs driving differences between groups and find that many are associated with genes that may be relevant to local adaptation to environmental chemicals such as host plant defenses or chemicals introduced by human activity, notably to do with metabolism and detoxification. While much field work remains to investigate any cryptic or phenotypic patterns as well as quantify effective migration, we hope that this work will inform refinement of conservation plans for one of Hawaiʻi’s two native butterflies.

Biochar-based slow/controlled-release fertilizer for sustainable agriculture: Recent advances, challenges and future prospects - D.H.H. Sim; I.A.W. Tan; L.L.P. Lim; F.K.S. Yeo; S. Phornvillay; M. Abat; Su Shiung Lam; B.H. Hameed (Journal of Environmental Chemical Engineering, 2025)

Assessing the impact of tidal inundation on the livelihood vulnerabilities of the Chattogram City dwellers in Bangladesh - Taj Sultana; M. Rezaul Islam; Firuza Begham Mustafa; Jillian Ooi Lean Sim (Natural Hazards, 2025)

Angiopoietin-2 binds to FGFR2, inhibits FGF-FGFR2 signaling, and delays cutaneous wound healing by inhibiting wound angiogenesis - Minji Sim; Hidetaka Ohnuki; Stewart Durell; Haydar Bulut; Yuyi Wang; Marzena Dyba; Sergey G. Tarasov; Lisa M. Jenkins; Giovanna Tosato (Angiogenesis, 2025)
Wound healing is an essential repair process, and impaired wound healing is a common and sometimes debilitating medical problem. Despite advances in wound healing approaches, optimal management strategies are lacking, partly due to an incomplete understanding of the complex pathophysiology of this process. Here we show that Ang2, a previously known ligand for the Tie2 receptor, also binds to fibroblast growth factor receptor 2 (FGFR2) independently of Tie2 and attenuates FGF/FGFR2 signaling in endothelial cells. Functionally, Ang2 inhibits endothelial cell migration induced by FGF. In mouse, topical Ang2 delays the healing of skin wounds, associated with reduced wound angiogenesis and recruitment of mesenchymal-type cells. Additionally, topical AMG386, a blocker of Ang1/Ang2 binding to Tie2 and systemic REGN910, a blocker of Ang2 binding to Tie2, accelerate wound repair, associated with increased wound angiogenesis and recruitment of inflammatory cells. These results identify the tyrosine kinase FGFR2 as a previously unrecognized Ang2 receptor, explaining some of the context-dependent functions of Ang2 in endothelial cells. Since Ang2 is induced in cutaneous wounds and endogenous FGF/FGFR2 is essential for wound repair, Ang2 blockade holds promise as a new evidence-based therapeutic option to promote wound repair.

Validation of a laboratory craving assessment and evaluation of 4 different interventions on cravings among adults with overweight or obesity - Ellen K. Pasquale; David R. Strong; Dawn M. Eichen; Carol B. Peterson; D. Eastern Kang-Sim; Kerri N. Boutelle (Appetite, 2024)

Recurrent selection shapes the genomic landscape of differentiation between a pair of host‐specialized haplodiploids that diverged with gene flow - Ashleigh N. Glover; Vitor C. Sousa; Ryan D. Ridenbaugh; Sheina B. Sim; Scott M. Geib; Catherine R. Linnen (Molecular Ecology, 2024)
Understanding the genetics of adaptation and speciation is critical for a complete picture of how biodiversity is generated and maintained. Heterogeneous genomic differentiation between diverging taxa is commonly documented, with genomic regions of high differentiation interpreted as resulting from differential gene flow, linked selection and reduced recombination rates. Disentangling the roles of each of these non‐exclusive processes in shaping genome‐wide patterns of divergence is challenging but will enhance our knowledge of the repeatability of genomic landscapes across taxa. Here, we combine whole‐genome resequencing and genome feature data to investigate the processes shaping the genomic landscape of differentiation for a sister‐species pair of haplodiploid pine sawflies, Neodiprion lecontei and Neodiprion pinetum . We find genome‐wide correlations between genome features and summary statistics are consistent with pervasive linked selection, with patterns of diversity and divergence more consistently predicted by exon density and recombination rate than the neutral mutation rate (approximated by dS). We also find that both global and local patterns of F ST , d XY and π provide strong support for recurrent selection as the primary selective process shaping variation across pine sawfly genomes, with some contribution from balancing selection and lineage‐specific linked selection. Because inheritance patterns for haplodiploid genomes are analogous to those of sex chromosomes, we hypothesize that haplodiploids may be especially prone to recurrent selection, even if gene flow occurred throughout divergence. Overall, our study helps fill an important taxonomic gap in the genomic landscape literature and contributes to our understanding of the processes that shape genome‐wide patterns of genetic variation.

No need to change recipes! Merely swapping meals on a weekly menu reduces carbon footprint and intake of saturated fatty acids - Annika N. Flynn; Taro Takahashi; Caroline Wynn; Alex Sim; Jeffrey M. Brunstrom (Appetite, 2024)

No need to change recipes! Merely swapping meals on a weekly menu reduces carbon footprint and intake of saturated fatty acids - Annika N. Flynn; Taro Takahashi; Caroline Wynn; Alex Sim; Jeffrey M. Brunstrom (Appetite, 2024)

Nanoneedles like FeP engineered on Ni-Foam as an effective catalyst towards overall alkaline freshwater, urea, and seawater splitting - Anjali Gupta; Cassia A. Allison; Rishabh Srivastava; Anuj Kumar; Mina Sim; Jeffery Horinek; Wang Lin; Felipe M. de Souza; Sanjay R. Mishra; Felio Perez; Ram K. Gupta; Tim Dawsey (Fuel, 2024)

Complexity of consumer acceptance to alternative protein foods in a multiethnic Asian population: A comparison of plant-based meat alternatives, cultured meat, and insect-based products - Airu Chia; Yiyun Shou; Nicole Min Yee Wong; David Cameron-Smith; Xueling Sim; Rob M. Van Dam; Mary F.-F. Chong (Food Quality and Preference, 2024)

Machine learning-driven hyperspectral imaging for non-destructive origin verification of green coffee beans across continents, countries, and regions - Joy Sim; Yash Dixit; Cushla Mcgoverin; Indrawati Oey; Russell Frew; Marlon M. Reis; Biniam Kebede (Food Control, 2024)

CQDs embed g-C3N4 photocatalyst in dye removal and hydrogen evolution: An insight review - Solayman H. M.; Azrina Abd Aziz; Noor Yahida Yahya; Kah Hon Leong; Lan Ching Sim; Md. Kamal Hossain; Md. Badiuzzaman Khan; Kyung-Duk Zoh (Journal of Water Process Engineering, 2024)

Characterisation and optimisation of M. oleifera for the removal of humic substances from peat water - U. Z. Seterik; D. Kanakaraju; Siong Fong Sim; L. M. Bilung (International Journal of Environmental Science and Technology, 2024)

Boosting oxygen evolution reaction activity with Mo incorporated NiFe-LDH electrocatalyst for efficient water electrolysis - Asiya M. Tamboli; Younghan Jung; Junseok Sim; Bonghyun Kim; Wan Sik Kim; MinJoong Kim; Changsoo Lee; Kilwon Kim; ChangHyuck Lim; KyongHwan Kim; Hyun-Seok Cho; Chang-Hee Kim (Chemosphere, 2023)

Support vector regression for prediction of stable isotopes and trace elements using hyperspectral imaging on coffee for origin verification - Joy Sim; Yash Dixit; Cushla Mcgoverin; Indrawati Oey; Russell Frew; Marlon M. Reis; Biniam Kebede (Food Research International, 2023)

Land use diversification may mitigate on‐site land use impacts on mammal populations and assemblages - Koen J. J. Kuipers; Sarah Sim; Jelle P. Hilbers; Stefanie K. van den Berg; Melinda M. J. de Jonge; Krista Trendafilova; Mark A. J. Huijbregts; Aafke M. Schipper (Global Change Biology, 2023)
Land use is a major cause of biodiversity decline worldwide. Agricultural and forestry diversification measures, such as the inclusion of natural elements or diversified crop types, may reduce impacts on biodiversity. However, the extent to which such measures may compensate for the negative impacts of land use remains unknown. To fill that gap, we synthesised data from 99 studies that recorded mammal populations or assemblages in natural reference sites and in cropland and forest plantations, with or without diversification measures. We quantified the responses to diversification measures based on individual species abundance, species richness and assemblage intactness as quantified by the mean species abundance indicator. In cropland with natural elements, mammal species abundance and richness were, on average, similar to natural conditions, while in cropland without natural elements they were reduced by 28% and 34%, respectively. We found that mammal species richness was comparable between diversified forest plantations and natural reference sites, and 32% lower in plantations without natural elements. In both cropland and plantations, assemblage intactness was reduced compared with natural reference conditions, but the reduction was smaller if diversification measures were in place. In addition, we found that responses to land use were modified by species traits and environmental context. While habitat specialist populations were reduced in cropland without diversification and in forest plantations, habitat generalists benefited. Furthermore, assemblages were impacted more by land use in tropical regions and landscapes containing a larger share of (semi)natural habitat compared with temperate regions and more converted landscapes. Given that mammal assemblage intactness is reduced also when diversification measures are in place, special attention should be directed to species that suffer from land use impacts. That said, our results suggest potential for reconciling land use and mammal conservation, provided that the diversification measures do not compromise yield.

Nitrate: The Dr. Jekyll and Mr. Hyde of human health? - Catherine P. Bondonno; Liezhou Zhong; Nicola P. Bondonno; Marc Sim; Lauren C. Blekkenhorst; Alex Liu; Anjana Rajendra; Pratik Pokharel; Dorit W. Erichsen; Oliver Neubauer; Kevin D. Croft; Jonathan M. Hodgson (Trends in Food Science & Technology, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Impact of land cover, rainfall and topography on flood risk in West Java - Rahmawati Rahayu; Simon A. Mathias; Sim Reaney; Gianni Vesuviano; Rusmawan Suwarman; Agus M. Ramdhan (Natural Hazards, 2023)
Flooding represents around 32% of total disasters in Indonesia and disproportionately affects the poorest of communities. The objective of this study was to determine significant statistical differences, in terms of river catchment characteristics, between regions in West Java that reported suffering from flood disasters and those that did not. Catchment characteristics considered included various statistical measures of topography, land-use, soil-type, meteorology and river flow rates. West Java comprises 154 level 9 HydroSHEDS sub-basin regions. We split these regions into those where flood disasters were reported and those where they were not, for the period of 2009 to 2013. Rainfall statistics were derived using the CHIRPS gridded precipitation data package. Statistical estimates of river flow rates, applicable to ungauged catchments, were derived from regionalisation relationships obtained by stepwise linear regression with river flow data from 70 West Javanese gauging stations. We used Kolmogorov–Smirnov tests to identify catchment characteristics that exhibit significant statistical differences between the two sets of regions. Median annual maximum river flow rate (AMRFR) was found to be positively correlated with plantation cover. Reducing plantation land cover from 20 to 10% was found to lead to a modelled 38% reduction in median AMRFR. AMRFR with return periods greater than 10 years were found to be negatively correlated with wetland farming land cover, suggesting that rice paddies play an important role in attenuating extreme river flow events. Nevertheless, the Kolmogorov–Smirnov tests revealed that built land cover is the most important factor defining whether or not an area is likely to report flood disasters in West Java. This is presumably because the more built land cover, the more people available to experience and report flood disasters. Our findings also suggest that more research is needed to understand the important role of plantation cover in aggravating median annual maximum river flow rates and wetland farming cover in mitigating extreme river flow events.

A multi-centre retrospective study of Nocardia speciation and antimicrobial susceptibility in Queensland, Australia - B. Z. Sim; L. Aaron; C. Coulter; J. Parkes-Smith; T. Badrick; K. May; M. Armstrong; S. Hendry; L. Sundac; L. Dang; J. Ho; J. Hanson; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Adults with overweight or obesity use less efficient memory strategies compared to adults with healthy weight on a verbal list learning task modified with food words - Dawn M. Eichen; Dong-Jin E. Kang Sim; Sara L. Appleton-Knapp; David R. Strong; Kerri N. Boutelle (Appetite, 2023)

Assessment of Lymphoma and Other Hematologic Malignancies Training Needs Among Radiation Oncology Residents: a Brief Report - Jenna M. Kahn; Joanna C. Yang; Joachim Yahalom; Bouthaina S. Dabaja; Neha Vapiwala; Bradford S. Hoppe; Yolanda D. Tseng; Chelsea C. Pinnix; Rahul R. Parikh; Austin J. Sim; John P. Plastaras; Jillian R. Gunther (Journal of Cancer Education, 2023)

EGR3 regulates opioid-related nociception and motivation in male rats - Swarup Mitra; Shruthi A. Thomas; Jennifer A. Martin; Jamal Williams; Kristen Woodhouse; Ramesh Chandra; Jun Xu Li; Mary Kay Lobo; Fraser J. Sim; David M. Dietz (Psychopharmacology, 2022)

A systematic review of coastal community adaptation practices in response to climate change-induced tidal inundation - Taj Sultana; M. Rezaul Islam; Firuza Begham Mustafa; Jillian Ooi Lean Sim (Journal of Coastal Conservation, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Quaternary Structure Changes for PrPSc Predate PrPC Downregulation and Neuronal Death During Progression of Experimental Scrapie Disease - Ghazaleh Eskandari-Sedighi; Leonardo M. Cortez; Jing Yang; Nathalie Daude; Klinton Shmeit; Valerie Sim; David Westaway (Molecular Neurobiology, 2021)
Prion diseases are fatal neurodegenerative diseases in mammals with the unique characteristics of misfolding and aggregation of the cellular prion protein (PrP C ) to the scrapie prion (PrP Sc ). Although neuroinflammation and neuronal loss feature within the disease process, the details of PrP C /PrP Sc molecular transition to generate different aggregated species, and the correlation between each species and sequence of cellular events in disease pathogenesis are not fully understood. In this study, using mice inoculated with the RML isolate of mouse-adapted scrapie as a model, we applied asymmetric flow field-flow fractionation to monitor PrP C and PrP Sc particle sizes and we also measured seeding activity and resistance to proteases. For cellular analysis in brain tissue, we measured inflammatory markers and synaptic damage, and used the isotropic fractionator to measure neuronal loss; these techniques were applied at different timepoints in a cross-sectional study of disease progression. Our analyses align with previous reports defining significant decreases in PrP C levels at pre-clinical stages of the disease and demonstrate that these decreases become significant before neuronal loss. We also identified the earliest PrP Sc assemblies at a timepoint equivalent to 40% elapsed time for the disease incubation period; we propose that these assemblies, mostly composed of proteinase K (PK)–sensitive species, play an important role in triggering disease pathogenesis. Lastly, we show that the PK-resistant assemblies of PrP Sc that appear at timepoints close to the terminal stage have similar biophysical characteristics, and hence that preparative use of PK-digestion selects for this specific subpopulation. In sum, our data argue that qualitative, as well as quantitative, changes in PrP conformers occur at the midpoint of subclinical phase; these changes affect quaternary structure and may occur at the threshold where adaptive responses become inadequate to deal with pathogenic processes.

Impact of formulary interventions on the minimum inhibitory concentration of methicillin-resistant Staphylococcus aureus to mupirocin, chlorhexidine, and octenidine in a Singapore tertiary institution - Shuwei Zheng; S. J. Chung; H. C. J. Sim; T. M. Chlebicka; Y. H. Chan; T. P. Lim; L. H. A. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Kappa opioid receptors mediate an initial aversive component of paclitaxel-induced neuropathy - Julie A. Meade; Y. Alkhlaif; K. M. Contreras; S. Obeng; W. Toma; L. J. Sim-Selley; D. E. Selley; M. I. Damaj (Psychopharmacology, 2020)

Ty-6, a major begomovirus resistance gene on chromosome 10, is effective against Tomato yellow leaf curl virus and Tomato mottle virus - Upinder Gill; John W. Scott; Reza Shekasteband; Eben Ogundiwin; Cees Schuit; David M. Francis; Sung-Chur Sim; Hugh Smith; Samuel F. Hutton (Theoretical and Applied Genetics, 2019)

Transpacific coalescent pathways of coconut rhinoceros beetle biotypes: Resistance to biological control catalyses resurgence of an old pest - Jonathan Bradley Reil; Camiel Doorenweerd; Michael San Jose; Sheina B. Sim; Scott M. Geib; Daniel Rubinoff (Molecular Ecology, 2018)
Biological control agents have several advantages over chemical control for pest management, including the capability to restore ecosystem balance with minimal non‐target effects and a lower propensity for targets to develop resistance. These factors are particularly important for invasive species control. The coconut rhinoceros beetle ( Oryctes rhinoceros Linnaeus) is a major palm pest that invaded many Pacific islands in the early 20th century through human‐mediated dispersal. Application of the Oryctes nudivirus in the 1960s successfully halted the beetle's first invasion wave and made it a textbook example of successful biological control. However, a recently discovered O. rhinoceros biotype that is resistant to the nudivirus appears to be correlated with a new invasion wave. We performed a population genomics analysis of 172 O. rhinoceros from seven regions, including native and invasive populations, to reconstruct invasion pathways and explore correlation between recent invasions and biotypes. With dd RAD sequencing, we generated data sets ranging from 4,000 to 209,000 loci using stacks and ipyrad software pipelines and compared genetic signal in downstream clustering and phylogenetic analyses. Analysis suggests that the O. rhinoceros resurgence is mediated by the nudivirus‐resistant biotype. Genomic data have been proven essential to understanding the new O. rhinoceros biotype's invasion patterns and interactions with the original biotype. Such information is crucial to optimization of strategies for quarantine and control of resurgent pests. Our results demonstrate that while invasions are relatively rare events, new introductions can have significant ecological consequences, and quarantine vigilance is required even in previously invaded areas.

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Population genomics and comparisons of selective signatures in two invasions of melon fly, Bactrocera cucurbitae (Diptera: Tephritidae) - Julian R. Dupuis; Sheina B. Sim; Michael San Jose; Luc Leblanc; M. Aftab Hoassain; Daniel Rubinoff; Scott M. Geib (Biological Invasions, 2018)

The impact of sustained hot weather on risk of acute work-related injury in Melbourne, Australia - Judith Anne McInnes; Ewan M. MacFarlane; Malcolm R. Sim; Peter Smith (International Journal of Biometeorology, 2018)

Integrative taxonomy reveals too extensive lumping and a new species in the moss genus Amphidium (Bryophyta) - Manuela Sim-Sim; Olga M. Afonina; Tereza Almeida; Aurélie Désamoré; Benjamin Laenen; César Augusto Garcia; Juana M. González-Mancebo; Michael Stech (Systematics and Biodiversity, 2017)

Developing an ecologically relevant heterogeneous biofilm model for dental-unit waterlines - Sham Lal; Mark Pearce; Undine E. M. Achilles-Day; John G. Day; L. H. Glyn Morton; St. John Crean; Sim K. Singhrao (Biofouling, 2017)

Seven days of high carbohydrate ingestion does not attenuate post-exercise IL-6 and hepcidin levels - Claire E. Badenhorst; Brian Dawson; Gregory R. Cox; Marc Sim; Coby M. Laarakkers; Dorine W. Swinkels; Peter Peeling (European Journal of Applied Physiology, 2016)

Genome‐wide set of SNP s reveals evidence for two glacial refugia and admixture from postglacial recolonization in an alpine ungulate - Zijian Sim; Jocelyn C. Hall; Bill Jex; Troy M. Hegel; David W. Coltman (Molecular Ecology, 2016)
Past glaciation events have played a major role in shaping the genetic diversity and distribution of wild sheep in North America. The advancement of glaciers can isolate populations in ice‐free refugia, where they can survive until the recession of ice sheets. The major Beringian refugium is thought to have held thinhorn sheep ( Ovis dalli ) populations during times of glacial advance. While isolation in the major refugium can account for much of the genetic and morphological diversity seen in extant thinhorn sheep populations, mounting evidence suggests the persistence of populations in smaller minor refugia. We investigated the refugial origins of thinhorn sheep using ~10 000 SNP s obtained via a cross‐species application of the domestic sheep ovine HD BeadChip to genotype 52 thinhorn sheep and five bighorn sheep ( O. canadensis ) samples. Phylogenetic inference revealed a distinct lineage of thinhorn sheep inhabiting British Columbia, which is consistent with the survival of a group of thinhorn sheep in a minor refugium separate from the Beringian refugium. Isolation in separate glacial refugia probably mediated the evolution of the two thinhorn sheep subspecies, the white Dall's sheep ( O. d. dalli ), which persisted in Beringia, and the dark Stone's sheep ( O. d. stonei ), which utilized the minor refugium. We also found the first genetic evidence for admixture between sheep from different glacial refugia in south‐central Yukon as a consequence of post glacial expansion and recolonization. These results show that glaciation events can have a major role in the evolution of species inhabiting previously glaciated habitats and the need to look beyond established refugia when examining the evolutionary history of such species.

Risk Assessment for the Spread of Serratia marcescens Within Dental-Unit Waterline Systems Using Vermamoeba vermiformis - Sham Lal; Sim K. Singhrao; Undine E. M. Achilles-Day; L. H. Glyn Morton; Mark Pearce; StJohn Crean (Current Microbiology, 2015)

Conservation of Portuguese red-listed bryophytes species in Portugal: Promoting a shift in perspective on climate changes - C. Sérgio; C. A. Garcia; C. Vieira; H. Hespanhol; M. Sim-Sim; S. Stow; R. Figueira (Plant Biosystems, 2014)

Snapper ( Chrysophrys auratus ): a review of life history and key vulnerabilities in New Zealand - DM Parsons; CJ Sim‐Smith; M Cryer; MP Francis; B Hartill; EG Jones; A Le Port; M Lowe; J McKenzie; M Morrison; LJ Paul; C Radford; et al. (New Zealand Journal of Marine and Freshwater Research, 2014)
Snapper ( Chrysophrys auratus ) is an important coastal fish species in New Zealand for a variety of reasons, but the large amount of research conducted on snapper has not been reviewed. Here, we review life history information and potential threats for snapper in New Zealand. We present information on snapper life history, defining stages (eggs and larvae, juvenile and adult), and assess potential threats and knowledge gaps. Overall we identify six key points: 1. post‐settlement snapper are highly associated with certain estuarine habitats that are under threat from land‐based stressors. This may serve as a bottleneck for snapper populations; 2. the largest knowledge gaps relate to the eggs and larvae. Additional knowledge may help to anticipate the effects of climate change, which will likely have the greatest influence on these early life stages; 3. ocean acidification, from land‐based sources and from climate change, may be an important threat to larval snapper; 4. a greater understanding of population connectivity would improve certainty around the sustainability of fishery exploitation; 5. the collateral effects of fishing are likely to be relevant to fishery productivity, ecosystem integrity and enduser value; 6. our understanding of the interrelationships between snapper and other ecosystem components is still deficient.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

∆9-Tetrahydrocannabinol-dependent mice undergoing withdrawal display impaired spatial memory - Laura E. Wise; Stephen A. Varvel; Dana E. Selley; Jason M. Wiebelhaus; Kelly A. Long; Lisa S. Middleton; Laura J. Sim-Selley; Aron H. Lichtman (Psychopharmacology, 2011)

Identification of QTL associated with resistance to bacterial spot race T4 in tomato - Samuel F. Hutton; Jay W. Scott; Wencai Yang; Sung-Chur Sim; David M. Francis; Jeffrey B. Jones (Theoretical and Applied Genetics, 2010)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Immunoreactivity for high-affinity choline transporter colocalises with VAChT in human enteric nervous system - Andrea M. Harrington; Margaret Lee; Sim-Yee Ong; Eric Yong; Pamela Farmer; Cristal J. Peck; Chung W. Chow; John M. Hutson; Bridget R. Southwell (Cell and Tissue Research, 2010)

Molecular, phytochemical and morphological characterization of the liverwort genus Radula in Portugal (mainland, Madeira, Azores) - Michael Stech; Manuela Sim-Sim; M. Glória Esquível; Leena luís; Susana Fontinha; Carlos Lobo; César Garcia; Soraia Martins; Cristiana Vieira; José Barroso; Luis G. Pedro; A. Cristina S. Figueiredo (Systematics and Biodiversity, 2010)

Endotoxin exposure and lung cancer risk: a systematic review and meta-analysis of the published literature on agriculture and cotton textile workers - Virissa Lenters; Ioannis Basinas; Laura Beane-Freeman; Paolo Boffetta; Harvey Checkoway; David Coggon; Lützen Portengen; Malcolm Sim; Inge M. Wouters; Dick Heederik; Roel Vermeulen (Cancer Causes & Control, 2010)

Identification of high-mannose and multiantennary complex-type N-linked glycans containing α-galactose epitopes from Nurse shark IgM heavy chain - David J. Harvey; Max Crispin; Beryl E. Moffatt; Sylvia L. Smith; Robert B. Sim; Pauline M. Rudd; Raymond A. Dwek (Glycoconjugate Journal, 2009)

Pharmacophore based 3D-QSAR study of VEGFR-2 inhibitors - M. M. Neaz; F. A. Pasha; M. Muddassar; So Ha Lee; Taebo Sim; Jung-Mi Hah; Seung Joo Cho (Medicinal Chemistry Research, 2009)

The use of modelling and simulation approach in reconstructing past landscapes from fossil pollen data: a review and results from the POLLANDCAL network - Marie-José Gaillard; Shinya Sugita; M. Jane Bunting; Richard Middleton; Anna Broström; Christopher Caseldine; Thomas Giesecke; Sophie E. V. Hellman; Sheila Hicks; Kari Hjelle; Catherine Langdon; Anne-Birgitte Nielsen; et al. (Vegetation History and Archaeobotany, 2008)

Identification of random amplified polymorphic DNA (RAPD) marker for differentiating male from female and sporophytic thalli of Gracilaria changii (Rhodophyta) - M. C. Sim; P. E. Lim; S. Y. Gan; S. M. Phang (Journal of Applied Phycology, 2007)

Occupational exposure to ionizing and non-ionizing radiation and risk of non-Hodgkin lymphoma - Ken K. Karipidis; Geza Benke; Malcolm R. Sim; Timo Kauppinen; Anne Kricker; Ann Maree Hughes; Andrew E. Grulich; Claire M. Vajdic; John Kaldor; Bruce Armstrong; Lin Fritschi (International Archives of Occupational and Environmental Health, 2007)

Ecological regime shifts in salinised wetland systems. I. Salinity thresholds for the loss of submerged macrophytes - Lien L. Sim; Jane M. Chambers; Jenny A. Davis (Hydrobiologia, 2006)

Ecological regime shifts in salinised wetland systems. II. Factors affecting the dominance of benthic microbial communities - Lien L. Sim; Jenny A. Davis; Jane M. Chambers (Hydrobiologia, 2006)

Genetic linkage mapping of an annual × perennial ryegrass population - S. E. Warnke; R. E. Barker; Geunhwa Jung; Sung-Chur Sim; M. A. Rouf Mian; M. C. Saha; L. A. Brilman; M. P. Dupal; J. W. Forster (Theoretical and Applied Genetics, 2004)

The impact of factor XIIIa V34L polymorphism on plasma factor XIII activity in the Chinese and Asian Indians from Singapore - Chew-Kiat Heng; Suman Lal; Nilmani Saha; Poh-Sim Low; M. Ilyas Kamboh (Human Genetics, 2004)

Virus Isolation for Diagnosing Dengue Virus Infections in Returning Travelers - D. Teichmann; K. Gbels; M. Niedrig; J.-W. Sim-Brandenburg; J. Lge-Stehr; M. P. Grobusch (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Molecular evolutionary analysis of the widespread piggyBac transposon family and related "domesticated" sequences - A. Sarkar; C. Sim; Y. S. Hong; J. R. Hogan; M. J. Fraser; H. M. Robertson; F. H. Collins (Molecular Genetics and Genomics, 2003)

Construction of a BAC library and generation of BAC end sequence-tagged connectors for genome sequencing of the African malaria mosquito Anopheles gambiae - Y. S. Hong; J. R. Hogan; X. Wang; A. Sarkar; C. Sim; B. J. Loftus; C. Ren; E. R. Huff; J. L. Carlile; K. Black; H.-B. Zhang; M. J. Gardner; et al. (Molecular Genetics and Genomics, 2003)

Pollen sequence from the Chilean Lake District during the Llanquihue glaciation in marine Oxygen Isotope Stages 4-2 - Calvin J. Heusser; Thomas V. Lowell; Linda E. Heusser; Andrs Moreira M.; Simn Moreira M. (Journal of Quaternary Science, 2000)

Deglacial palaeoclimate at Puerto del Hambre, subantarctic Patagonia, Chile - Calvin J. Heusser; Linda E. Heusser; Thomas V. Lowell; Andrs Moreira M.; Simn Moreira M. (Journal of Quaternary Science, 2000)

Expression of glutamate receptor subunits 2/3 and 4 in the hypoglossal nucleus of the rat after neurectomy - Feng-Ru Tang; M.-K. Sim (Experimental Brain Research, 1997)

Erratum - Sopheak K. Sim; Sarah M. Ohmann; Cindy B. S. Tong (American Journal of Potato Research, 1997)

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)

Comparison of polyphenol oxidase in tubers ofSolanum tuberosum and the non-browning tubers ofS. hjertingii - Sopheak K. Sim; Sarah M. Ohmann; Cindy B. S. Tong (American Journal of Potato Research, 1997)

Linear and nonlinear stiffness and friction in biological rhythmic movements - P. J. Beek; R. C. Schmidt; A. W. Morris; M. -Y. Sim; M. T. Turvey (Biological Cybernetics, 1995)